Indexing Geopolitical World; Code Preference and Inscription at Old Town Semarang, Indonesia - Khasanah, Nurul; Artawa, Ketut; Purnawati, Ketut Widya; Suryati, Ni Made (Randwick International of Social Science Journal, 2025)
Public sign at old town Semarang represents many variations of language. Besides, the history of old town Semarang offers something fresh perspective on Linguistic landscape due to Dutch colonialism. This study aims to analyze the signs and its relation with geopolitical world by considering government regulation and the purpose of the sign. This study used descriptive qualitative method. The study is phenomenological which is combinatorial, explanatory, and synchronic because the code preference and inscription used in public area (Bungin, 2017). The data were obtained through observation and documentation methods involving photography techniques. The data was analyzed using Scollon & Wong Scollon (2003). The result reveals three types of language used; mono/bi/multilingual form in 63 signs around old town Semarang with 15 different languages. All signs divided into four preferences. Among those signs, geopolitical effect was found through government’s regulation and it is indexing a power to set the public sign. Therefore, other signs were built by the sign maker for a commercial strategy. Despite the fact that the old town has Dutch history, English appeared as the most prominent language in the signs, indicating that language is not always in line with language protection and preservation goals.